Revitalizing Pesantren-Based Character Education at SPM Madrasah Ulya PP. Miftahul Mubtadiin for Global Harmony - Yusuf, M. (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study explores the revitalization of character education through pesantren traditions at Satuan Pendidikan Muadalah (SPM) Madrasah Ulya PP. Miftahul Mubtadiin, located in Krempyang, Nganjuk, East Java, Indonesia. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis to gain a rich understanding of the learning environment. The research aims to examine how pesantren-based practices cultivate love, peace, and tolerance while preparing students to engage with a multicultural and global society. Findings reveal that daily rituals, communal learning, and the integration of classical Islamic texts create a holistic educational atmosphere that strengthens moral character, nurtures religious moderation, and promotes social responsibility and humanitarian awareness. These practices demonstrate the relevance of local wisdom in responding to contemporary global challenges, particularly in fostering a culture of peace, strengthening social cohesion, and developing resilient moral values among young generations. The study concludes that pesantren traditions provide a sustainable model of character education that is contextually rooted yet universally applicable to efforts for global harmony.